Rethinking Third Cinema - Guneratne, Anthony R.; Dissanayake, Wimal; Chakravarty, Sumita S. (Routledge, 2003)
This important anthology addresses established notions about Third Cinema theory, and the cinema practice of developing and postcolonial nations. The 'Third Cinema' movement called for a politicised film-making practice in Africa, Asia and Latin America, one which would take on board issues of race, class, religion, and national integrity. The films which resulted from the movement, from directors such as Ousmane Sembene, Satyajit Ray and Nelson Pereira dos Santos, are among the most culturally signficant, politically sophisticated and frequently studied films of the 1960s and 1970s. However, despite the contemporary popularity and critical attention enjoyed by films from Asia and Latin America in particular, Third Cinema and Third Cinema theory appears to have lost its momentum. Rethinking Third Cinema seeks to bring Third Cinema and Third Cinema theory back into the critical spotlight. The contributors address the most difficult and challenging questions Third Cinema poses, suggesting new methodologies and redirections of existing ones. Crucially, they also re-examine the entire phenomenon of film-making in a fast-vanishing 'Third World', with case studies of the cinemas of India, Iran and Hong Kong, among others.